Anatomical characterization and chemical profile of Laguncularia racemosa (L.) Gaertn leaf blades, from impacted and non-impacted mangroves of the São Paulo Coast - Silva, Joao Marcelo; Goncalves Martins, Maria Bernadete [UNESP]; Cavalheiro, Alberto José [UNESP] (Fundação Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2010)
Anatomical characterization and chemical profile of Laguncularia racemosa (L.) Gaertn leaf blades, from impacted and non-impacted mangroves of the São Paulo Coast. Several sources of environmental impact have caused great damage to the flora in mangroves. Therefore, this study aimed to analyze the anatomy and chemical composition of Laguncularia racemosa (L.) Gaertn leaf blades, from impacted (Municipality of Santos) and non-impacted mangroves (Municipality of Peruibe) of the São Paulo Coast. For the leaf anatomy studies, light microscopy and scanning electron microscopy (SEM) were used. For chemical analysis, high performance liquid chromatography (HPLC) was conducted. The biometry revealed leaf tissues of plants from impacted mangroves with a less thick epidermis and mesophyll and higher width of the central vascular beam. A smaller number of stomata and higher amounts of daises in these leaves were also observed. Results were confirmed by the Student t-test (alpha = 5%). The chemical profiles revealed a higher ammount of secondary metabolites in leaves from the impacted environment.
Keywords: leaf anatomy; environmental impact; Santos; Peruibe